(untitled) (Bangladesh Veterinarian, 2010)
Two vaccination regimens against Newcastle disease were compared. A total of 180 crossbred (RIR × Fayoumi) day-old chicks were obtained from the government Poultry Farm. At three days of age, 10 birds were randomly selected and killed to obtain blood samples for serum collection. The remaining 170 birds were divided into three groups. Group A, (55) received a locally produced live lentogenic Newcastle disease virus (NDV) vaccine called “Baby Chick Ranikhet Disease Vaccine” (BCRDV) intraocularly at three and 28 days of age followed by a live mesogenic NDV vaccine namely “Ranikhet Disease Vaccine” (RDV) intramuscularly at 60 days of age. Group B, (55) was vaccinated with an imported live lentogenic commercial vaccine intraocularly at three, 28 and 60 days of age. Group C, (60) served as unvaccinated control. Further blood samples were collected on day 28, 60 and 74 from all groups. All the sera were tested for haemagglutination inhibition (HI) antibody titre to NDV. At 75 days of age, 30 birds from each of the two vaccinated groups and 32 birds from the unvaccinated group were challenged with a velogenic viscerotropic field isolate of NDV. The chicks had a high level of maternal HI antibodies at three days of age with a geometric mean titre (GMT) of log2 4.8, but that gradually declined in the unvaccinated group. Following vaccination there was no remarkable rise in the antibody titre at 28 and 60 days of age (GMT>log2 3.5), but at 74 days of age, the GMT of HI antibody in Group A (log2 5.9) was significantly higher than that in the Group B (log2 4.1). Following challenge, 100% morbidity and 65.6% mortality were observed in the unvaccinated group. Among the vaccinated groups, only 16.7% morbidity and no mortality were noticed in Group A but 43.3% morbidity and 10% mortality were observed in Group B. It is suggested that a vaccination programme based on lentogenic priming and mesogenic booster gave better protection against velogenic viscerotropic NDV challenge than that based on lentogenic vaccine only. (Bangl. vet. 2010. Vol. 27, No. 1, 1 – 7) DOI: 10.3329/bvet.v27i1.5908